2023
DOI: 10.7717/peerj.15347
|View full text |Cite
|
Sign up to set email alerts
|

Association between free thyroxine levels and clinical phenotype in first-episode psychosis: a prospective observational study

Abstract: Aim To determine whether thyroid hormone levels are associated with a specific clinical phenotype in patients with first-episode psychosis (FEP). Methods Ninety-eight inpatients experiencing FEP and with less than 6 weeks of antipsychotic treatment were included in the study and were followed up for one year. Baseline psychiatric evaluation included assessment of prodromal symptoms, positive and negative symptoms, depressive symptoms, stres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Previous studies have established associations of serum biomarkers related to inflammatory ( 50 – 52 ), oxidative stress ( 53 ), immune ( 54 ), neuroendocrine ( 55 ), and metabolic systems ( 56 ) with the DUP. To our knowledge, the current study is the first to report that a CSF biomarker related to brain bioenergetics is correlated with the DUP.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have established associations of serum biomarkers related to inflammatory ( 50 – 52 ), oxidative stress ( 53 ), immune ( 54 ), neuroendocrine ( 55 ), and metabolic systems ( 56 ) with the DUP. To our knowledge, the current study is the first to report that a CSF biomarker related to brain bioenergetics is correlated with the DUP.…”
Section: Discussionmentioning
confidence: 99%
“…Only a few studies have explored the relationship between clinical symptoms and alterations in thyroid hormone levels. Recently, one study in FEP patients ( 33 ) found that high T4 plasma levels (but still within the normal range) were associated with fewer prodromal symptoms, shorter DUP, greater likelihood of sudden onset psychosis, and more affective symptomatology at 1 year of follow-up. A study involving patients with early psychosis found that higher T4 levels were associated with better cognitive performance on the attention domain ( 12 ) and that the presence of antithyroid antibodies was associated with worse negative symptoms ( 9 ).…”
Section: Discussionmentioning
confidence: 99%